Nozioni di base della lingua italiana per il settore del turismo - Kompara Lukančič, Mojca (2020)
Basics of the Italian Language for the Field of Tourism: Second Edition. The professional monograph Basics of the Italian Language for the Field of Tourism – Second edition represents an excellent basis for all those who work in the field of tourism and use the Italian language. The monograph includes 5 sectors and 34 units, which offer the reader both theoretical notions and their application in the language of tourism. The reader has the opportunity to enrich their vocabulary thanks to the authentic texts of various subfields such as hotel, catering, tourist destinations, gastronomy and winemaking, wellness and selfness. Nevertheless, the topics discussed are not limited exclusively to the tourism field, but also include cultural concepts, which encompass multidisciplinary and multicultural points of view, providing the reader with a complete view of the basics of the Italian language forthe field of tourism.La monografia professionale Nozioni di base della lingua italiana per il settore del turismo – Seconda edizione rappresenta una base eccellente per tutti coloro che operano nel campo del turismo e usano la lingua italiana. La monografia comprende 5 settori e 34 unità, che offrono al lettore sia nozioni teoriche sia l'applicazione delle stesse nel linguaggio settoriale del turismo. Il lettore ha la possibilità di arricchire il proprio vocabolario settoriale del turismo grazie ai testi autentici di vari settori come quello alberghiero, la ristorazione, le destinazioni turistiche, la gastronomia e la vinificazione, il wellness e il selfness. Ciononostante, gli argomenti discussi non si limitano esclusivamente al settore del turismo, ma includono anche concetti culturali, che racchiudono punti di vista multidisciplinari e multiculturali, fornendo al lettore una visione completa delle basi della lingua italiana nel settore del turismo.1st reprint of the 2nd edition - COBISS.SI ID: 108713987
Keywords: Italian; tourism; Italy; terminology; grammar; italiano; turismo; Italia; terminologia; grammatica